A STUDY COMPARING SOCIO-DEMOGRAPHIC AND CLINICAL PROFILE OF PATIENTS OF UNIPOLAR AND BIPOLAR DEPRESSION. - fatma, Dr. Farheen; Dr .Dhruv (Student’s Journal of Health Research Africa, 2023)
Background: Unipolar and bipolar depression are distinct in symptoms, diagnosis, prognosis, course of treatment, neurobiology, and genetics. The study aims to compare the subjective variables linked to bipolar and unipolar depression in inpatients. This study also aimed to investigate the psychosocial and demographic factors that affect bipolar and unipolar depression. Materials and Methods: 152 patients both males and females classified, into group I (unipolar) and group II (bipolar). The clinical profile and socio-demographic profile of both were recorded. The collected data was analyzed statistically. Patients who fulfilled the inclusion criteria were included in this study. Results: The difference was significant between the two groups i.e., unipolar and bipolar depression. A value of P less than 0.05 is considered significant. 60% of the unipolar group reported severe depression without psychotic symptoms compared to 80% of the bipolar group who had severe depression with psychotic symptoms. Group I & II parameters are relatively different as Delusions were seen in 30 and 2, panic symptoms in 22 and 14, anhedonia in 42 and 26, suicidal thoughts in 2 and 5, pseudodementia in 6 and 2, and depressive cognitions in 10 and 6 respectively. Conclusion: The authors found that patients with bipolar and unipolar depression have different QOL profiles. With the introduction of bipolar spectrum, Adequate measures should be taken to understand the clinical markers of bipolarity. It is important to understand the signs of the disorder to determine the precise neurobiology of bipolarity and to forecast its course, more research is required. Recommendation: A second drug is recommended if the patient presents while the condition is already managed with lithium monotherapy.